2006
DOI: 10.1186/1471-2164-7-227
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization and evolution of the ULBP genes in cattle

Abstract: Background: The cattle UL16-binding protein 1 (ULBP1) and ULBP2 genes encode members of the MHC Class I superfamily that have homology to the human ULBP genes. Human ULBP1 and ULBP2 interact with the NKG2D receptor to activate effector cells in the immune system. The human cytomegalovirus UL16 protein is known to disrupt the ULBP-NKG2D interaction, thereby subverting natural killer cell-mediated responses. Previous Southern blotting experiments identified evidence of increased ULBP copy number within the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Finally, gene conversion has played a major role in shaping the IFNA gene family in eutherian species after gene duplication [ 44 , 45 ]. The other duplication examples include TCRV [ 46 ], C-type lysozymes [ 29 ], BPI-like ( BSP30 ) [ 47 ], BPI / LBP , Cathelicidin [ 29 ], interferon subfamilies ( IFNB , IFNW , and IFNX ) [ 29 ], Pregnancy-associated glycoprotein [ 48 ], Sulfotransferases, ULBP [ 49 ], WC1 [ 50 ] and etc.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, gene conversion has played a major role in shaping the IFNA gene family in eutherian species after gene duplication [ 44 , 45 ]. The other duplication examples include TCRV [ 46 ], C-type lysozymes [ 29 ], BPI-like ( BSP30 ) [ 47 ], BPI / LBP , Cathelicidin [ 29 ], interferon subfamilies ( IFNB , IFNW , and IFNX ) [ 29 ], Pregnancy-associated glycoprotein [ 48 ], Sulfotransferases, ULBP [ 49 ], WC1 [ 50 ] and etc.…”
Section: Resultsmentioning
confidence: 99%
“…To highlight the potential evolutionary contributions of these CNVs to cattle breed formation and adaptation, we conservatively queried out 35 CNVRs that have high-confidence breed-specific CNV frequency differences (Supplemental Table S12). Twenty-nine of these CNVRs correspond to annotated genes or gene families, while many of them are also known in other mammals to interact with environments, some of them are known to be important in cattle adaptation including SCP2 (Liu et al 2009), ULBP (Larson et al 2006), and WC1.1 (Herzig and Baldwin 2009). To our knowledge, this is the first systematic report on breed-specific copy number differences in cattle.…”
Section: Cattle Cnv Frequency Differences Among Breedsmentioning
confidence: 99%
“…4; Supplemental Table S13). After mapping of the ULBP major cluster (Larson et al 2006), we found within this region ULBP21 and ULBP2 are potential functional copies, while other copies are either partially overlapped (ULBP17 ) or pseudogenes (Supplemental Fig. S4).…”
Section: Cattle Cnv Frequency Differences Among Breedsmentioning
confidence: 99%
“…Mapped ULBP genes are all assigned to a 3.1 Mb region on chromosome 9. The organization of the ULBP gene cluster in the Hereford cattle differs from that of the Holstein cattle , both in terms of gene copy number and arrangement. Therefore, ULBP genes seem to display copy number variations across diverse breeds .…”
Section: Comparative Genomics Of the Ulbp Gene Familymentioning
confidence: 96%